An epidemiological study on morbidity profile and predictors of health seeking behaviour among elderly population in a tribal dominant state of India: A regression analysis - Santosh Kumar Soren; Shalini Sunderam; Manish Deo; Anit Kujur; Shashi Bhushan Singh; Atul Kachhap (Journal of Family Medicine and Primary Care, 2022)
Background: Ageing is defined as a process of deterioration in the functional capacity of an individual that results from structural changes, with the advancement of age. Globally the geriatric population has increased from 8% in 2012 to 8.5% in 2015 and expected to rise by 22% in 2050. Hence we planned to study morbidity profiles and predictors of health-seeking behaviour among the elderly population in Ormanjhi, Ranchi. Methodology: A community based cross sectional study was conducted in Ormanjhi, Ranchi, Jharkhand for a period of six months (March-August 2018). The study was done among 206 geriatric populations fulfilling the eligibility criteria, selected by cluster sampling and those not giving their consent were excluded from the study. Data collected were entered in Microsoft Excel and analysis was done on Statistical Package for Social Sciences (SPSS) version 20.0. Results: A total of 206 geriatric populations fulfilling the study criteria, were enrolled during the study. The majority of the age group was found between 60-69 years (71.8%). Around 202 (98.1%) of which resided in rural areas, nearly half 102 (49.5%) depended on pension for livelihood and 108 (52.4%) were illiterate. Two-fifth of the study subjects (40.3%) consulted a government doctor if any health problems occurred followed by 30.5% preferred a private doctor and 20.1% consulted unqualified practitioners. Most of the study participants (64.5%) did not seek medical care due to financial reasons followed by 14.5% considered it a minor illness than 13% complained that health facility far away and 8.1% considered that old age itself as a disease. Non tribal ethnicity, participants who had their own source of income and co-morbidity were significantly associated with health seeking behaviour. Conclusion: Most participants in this study suffered from morbidities which also affect their quality of life. It was also observed that most of them were not dependent on others for their daily activities. Health seeking behaviour was found to be appropriate in nearly two third (70%) of elderly subjects in Ranchi, Jharkhand.